Values of Character Education in the Tradition of Senandung Jolo - Gafar, Abdoel (Indonesian Research Journal in Education |IRJE|, 2024)
This research is motivated by preserving regional culture so that it does not disappear with the times and developing technology. Nowadays, the younger generation no longer recognizes the cultural heritage of the past. Therefore, this research aims to explore and introduce to the younger generation in Tanjung Village, Kumpeh Ilir District, Muaro Jambi Regency, an art of speaking called Senandung Jolo. The research method used in this research is qualitative descriptive. The research results show that Senandung Jolo is a pantun that is traditionally played using a simple musical instrument made of Mahang wood, which has been combined with a tambourine, drum, and guitar. From this senandung, character education values ​​about beauty are born and related to human behavior with God, oneself, fellow humans, and the environment. These results indicate that Senandung Jolo has character education values, ​​which can be used to instill character education values ​​in the younger generation and students at all school levels.